2017
DOI: 10.21767/1791-809x.1000514
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact Analysis of Cancer in the Health System of Brazil: Model Based in Public Database

Abstract: Objectives: To analyze the economic impact of cancer in the Brazilian health system from 2010 to 2015 and to forecast the impact until 2020.Methods: Public databases were used to estimate cancer costs to which were added hospitalization costs, outpatient visits and treatments. Indirect costs were added to the calculation of income loss caused by neoplasms morbidity or mortality. Results:The estimated costs amounted to INT$ 59.7 billion in the year 2015 with an exponential increase from 2010 to 2015. The costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
8
0
7
Order By: Relevance
“…Most establishments were licensed as UNACONs, resulting in the need to refer patients to external radiotherapy services, which may affect the optimal treatment time and compromise the therapy effectiveness. However, the status of cancer care in Brazil is poorly understood because of the limited availability of national data on cancer treatment outcomes and their correlation with institutional investments over time [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most establishments were licensed as UNACONs, resulting in the need to refer patients to external radiotherapy services, which may affect the optimal treatment time and compromise the therapy effectiveness. However, the status of cancer care in Brazil is poorly understood because of the limited availability of national data on cancer treatment outcomes and their correlation with institutional investments over time [29].…”
Section: Discussionmentioning
confidence: 99%
“…All the investment that will be employed will have a single outcome -death. Siqueira et al 18 , when analyzing the economic impact of cancer on the SUS, identified that although there is a historic increase in funding for cancer care, 63% of the total cost is related to cancer mortality. The revision of this logic is imperative.…”
Section: Financingmentioning
confidence: 99%
“…It is usual to observe in the reports issued by the Committee mentions to the lack of real-world data for Brazilian patients, which could support decision-making 24 . Despite the truth of the argument, the difficulties in carrying out these studies can not be denied, due to, the breaches in the care network, the lack of reliable information on therapies used in the institutions and on the non-existent measurement of clinical results stemming from practice 4,18 .…”
Section: Technologiesmentioning
confidence: 99%
“…In 2010, the estimates indicated the global annual economic cost of cancer at approximately US$ 1.16 trillion [ 11 ]. In Brazil, the total cost of cancer (including mortality and morbidity) was estimated at Int$ 59.7 billion in 2015 and projected to reach Int$ 81 billion in 2020 [ 12 ]. The cost of mortality represents 63% of the total costs of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Direct costs account for 20% ($10,025 per patient), and morbidity accounts for 17%. The Brazilian estimates of health expenditures were 9.5% of gross domestic product (GDP), with the average cost of cancer accounting for 1.7% of the GDP per year [ 12 ]. These results demonstrate the impact of cancer on society and the economy.…”
Section: Introductionmentioning
confidence: 99%